2018
DOI: 10.1017/s1751731117001951
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation and selection response for growth in meat-type quail through random regression models using B-spline functions and Legendre polynomials

Abstract: The objective was to estimate (co)variance functions using random regression models (RRM) with Legendre polynomials, B-spline function and multi-trait models aimed at evaluating genetic parameters of growth traits in meat-type quail. A database containing the complete pedigree information of 7000 meat-type quail was utilized. The models included the fixed effects of contemporary group and generation. Direct additive genetic and permanent environmental effects, considered as random, were modeled using B-spline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…There are quite a few differences between the live weight values of Japanese quails due to the domestication, adaptation to cage conditions and genetic selection studies. While body weight values at the age of six weeks have been reported as 100-130 g in some studies [34,35], these averages have been reported to be in the range of 250-300 g in other studies [36,37]. In studies in which the growth of Japanese quails was examined with the Gompertz model, the mature-weight parameter was found in the range of 224-295 g [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…There are quite a few differences between the live weight values of Japanese quails due to the domestication, adaptation to cage conditions and genetic selection studies. While body weight values at the age of six weeks have been reported as 100-130 g in some studies [34,35], these averages have been reported to be in the range of 250-300 g in other studies [36,37]. In studies in which the growth of Japanese quails was examined with the Gompertz model, the mature-weight parameter was found in the range of 224-295 g [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, because the covariance pattern among the repeated measurements of longitudinal traits is well structured, different statistical methods are required to better account for the trait structure compared with single-measurement traits. Today, analyses of longitudinal data are carried out mainly based on RRM (e.g., Mota et al, 2018a;Padilha et al, 2018;Saghi et al, 2018).…”
Section: Development Historymentioning
confidence: 99%
“…The popularity of RRM has increased substantially in animal breeding research over the past years, and RRM have been considered the method of choice to genetically evaluate longitudinal traits in various livestock species, including dairy cattle (e.g., Kheirabadi, 2018;Padilha et al, 2018), beef cattle (e.g., Oliveira et al, 2018a), sheep (e.g., Saghi et al, 2018), goats (e.g., Brito et al, 2018), horses (e.g., Bartolomé et al, 2018), swine (e.g., Huynh-Tran et al, 2017), poultry (e.g., Miyumo et al, 2018), quail (e.g., Mota et al, 2018a), and fish (e.g., Zhao et al, 2018).…”
Section: Applications Of Rrmmentioning
confidence: 99%
“…The choice of the covariance function used for modelling the additive genetic and permanent environmental effects is an important step for the implementation of RRM in genetic evaluations. Legendre orthogonal polynomials (LEG) are the most commonly used models in various livestock species (Brito et al, 2018; Lázaro et al, 2021; Li et al, 2020; Meyer, 2005; Mota et al, 2018; Oliveira et al, 2019). In addition, several studies have shown that LEG are appropriate for genetically modelling milk yield in dairy buffaloes (Aspilcueta‐Borquis et al, 2013, 2012; Breda et al, 2010; Hurtado‐Lugo et al, 2015; Lázaro et al, 2021; Sesana et al, 2010; Tonhati et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%